Utilization of Black Soldier Fly (BSF) Maggots for Organic Waste Decomposition at the Mustika Ikhlas Integrated Waste Management Facility, Tigaraksa, Tangerang Regency - Qiswatun Mukhoyyaroh; Latif Sofiana Nugraheni; Indah Anugerah Sari; Shabrina Nur Eka Amelia (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Waste management challenges in Tangerang have intensified due to the continuous increase in daily waste generation, which is not adequately supported by effective treatment systems, leading to waste accumulation and environmental degradation. This study aims to analyze the utilization of BSF maggots as a biological agent for organic waste decomposition at the Mustika Ikhlas Integrated Waste Management Facility (TPST), Tigaraksa. The research employed a descriptive qualitative approach conducted from November 2024 to June 2025. Data were collected through in-depth interviews with five key informants who were directly involved in organic waste management and BSF maggot cultivation activities. Data analysis was carried out using thematic analysis, encompassing data reduction, data display, and conclusion drawing. The findings reveal that the BSF maggot-based waste management process consists of several systematic stages, including organic waste sorting and collection, initial fermentation, controlled feeding, biodegradation by maggots, harvesting, utilization of harvested maggots as animal feed, and the reuse of residual media and larval exoskeletons as compost or soil enhancers. Based on field observations, 1 kg of adult BSF maggots can decompose approximately 10 kg of organic waste in 24 hours. Therefore, if the number of BSF maggots raised reaches 10 kg, the volume of organic waste that can be decomposed increases to approximately 100 kg in the same time period. These results indicate that BSF maggot utilization offers an effective, environmentally sustainable, and economically beneficial alternative for organic waste management. Furthermore, the study highlights the potential of BSF-based bioconversion as a scalable, integrated strategy for sustainable waste management in urban and peri-urban areas, particularly in regions with high organic waste generation. This research offers innovation in terms of research location (conducted at TPST Tigaraksa) and study focus (on the maggot cultivation process and its use in organic waste decomposition).